2019
DOI: 10.1242/jeb.182741
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic scaling of pelvic limb muscles, tendons and locomotor economy in the Ostrich (Struthio camelus)

Abstract: In rapidly growing animals there are numerous selective pressures and developmental constraints underpinning the ontogenetic development of muscle-tendon morphology and mechanical properties. Muscle force generating capacity, tendon stiffness, elastic energy storage capacity and efficiency were calculated from muscle and tendon morphological parameters and in vitro tendon mechanical properties obtained from a growth series of ostrich cadavers. Ontogenetic scaling relationships were established using reduced ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 80 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…In the greater rhea, the total limb muscle mass scaled with an exponent of 1.18 when tendons were included in the measurements; for individual muscles, M. tibialis cranialis and M. puboischiofemoralis showed isometric growth, and the remaining 17 muscles scaled with positive allometry (Picasso, 2015). Using a series of 18 samples aged from hatchling to 2 years, Channon et al (2019) considered 21 muscles in the ostrich and found that either total muscle mass, or individual muscle mass, scaled with strong positive allometry. However, in the emu, another precocial ratite bird, a comprehensive study showed that the muscle masses presented three scaling patterns: 26 muscles out of 34 were positively allometric, FPPD2 was negatively allometric, and 7 muscles (AM, FCL, FME, ITM, ITCR, ISF, IFI) were isometric (Lamas et al, 2014).…”
Section: Scaling Patterns Across Ontogenymentioning
confidence: 99%
See 2 more Smart Citations
“…In the greater rhea, the total limb muscle mass scaled with an exponent of 1.18 when tendons were included in the measurements; for individual muscles, M. tibialis cranialis and M. puboischiofemoralis showed isometric growth, and the remaining 17 muscles scaled with positive allometry (Picasso, 2015). Using a series of 18 samples aged from hatchling to 2 years, Channon et al (2019) considered 21 muscles in the ostrich and found that either total muscle mass, or individual muscle mass, scaled with strong positive allometry. However, in the emu, another precocial ratite bird, a comprehensive study showed that the muscle masses presented three scaling patterns: 26 muscles out of 34 were positively allometric, FPPD2 was negatively allometric, and 7 muscles (AM, FCL, FME, ITM, ITCR, ISF, IFI) were isometric (Lamas et al, 2014).…”
Section: Scaling Patterns Across Ontogenymentioning
confidence: 99%
“…Compared with the hip and thigh muscle group, the shank muscles are characterized by having obvious long tendons. Through ontogeny, these tendons undergo positive allometric or persistent isometric growth, suggesting that they may have enhanced or at least equivalent potential for elastic energy storage with increasing body size (Bennett, 1996;Channon et al, 2019;Lamas et al, 2014). Considering the muscle-tendon unit as a whole, a trade-off between muscle force and tendon elasticity should exist to provide economy and efficiency of locomotion during ontogeny.…”
Section: Distribution Of Muscle Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Ontogenetic changes in muscle architecture have also been studied in a range of other species [e.g. emu Dromaius novaehollandiae (Lamas et al ., 2014); ostrich (Channon et al ., 2019); eastern cottontail rabbit Sylvilagus floridanus (Butcher et al ., 2019); rat Rattus norvegicus domestica (Woittiez et al ., 1986)], including analyses of the contribution of differences in muscle properties to disparate gait, energetics and maximal performance in male versus female chickens across sexual maturity (Rose et al ., 2016a,b).…”
Section: Introductionmentioning
confidence: 99%